2008
DOI: 10.1021/cm800955f
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymers Bearing Iridium Complexes for Triplet Photovoltaic Devices

Abstract: The aim of this work is to investigate the effect of incorporating an iridium complex into a π-conjugated polymer backbone on photovoltaic properties such as charge generation, power conversion efficiency and external quantum efficiency (EQE). Poly(9,9-dihexylfluorene-co-2-phenylpyridine) (1) and poly(9,9dioctylfluorene-co-tris(2-phenylpyridine) iridium (III))) (2) were synthesized using Suzuki polycondensation. Characterization was performed using NMR, UV-vis, photoluminescence, and time-resolved luminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 17 publications
1
71
0
Order By: Relevance
“…The MEH-PPV/C 60 bilayer photovoltaic device without PtOEP attained a short-circuit current ( J sc ) of 0.3 mA cm The enhanced photocurrent and power-conversion effi ciency in the PtOEP blended MEH-PPV/C 60 bilayer photovoltaic device can be attributed to the increased population of long-lived, mobile triplet excitons in the conjugated polymer, which is consistent with our PIA results and previously published data. [7][8][9][10][11][12][13][14][15] The long exciton diffusion length of the triplet excitons increases intersystem crossing effi ciency of MEH-PPV. Similar to our results, Cleave et al, reported that the enhanced triplet-exciton population of poly[(2-methoxy-5-(3,7-dimethyl)-octyloxy)-1,4-phenylenevinylene] (OC 1 C 10 -PPV) originated from the triplettriplet energy transfer from PtOEP to OC 1 C 10 -PPV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEH-PPV/C 60 bilayer photovoltaic device without PtOEP attained a short-circuit current ( J sc ) of 0.3 mA cm The enhanced photocurrent and power-conversion effi ciency in the PtOEP blended MEH-PPV/C 60 bilayer photovoltaic device can be attributed to the increased population of long-lived, mobile triplet excitons in the conjugated polymer, which is consistent with our PIA results and previously published data. [7][8][9][10][11][12][13][14][15] The long exciton diffusion length of the triplet excitons increases intersystem crossing effi ciency of MEH-PPV. Similar to our results, Cleave et al, reported that the enhanced triplet-exciton population of poly[(2-methoxy-5-(3,7-dimethyl)-octyloxy)-1,4-phenylenevinylene] (OC 1 C 10 -PPV) originated from the triplettriplet energy transfer from PtOEP to OC 1 C 10 -PPV.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] In general, these conjugated polymers with aromatic structure show weak spin-orbit coupling and thus limit the generation of triplet excitons. [ 16 ] Nonetheless, the tripletexciton density of these conjugated polymers could be enhanced by increasing the intersystem crossing (ISC) effi ciency [7][8][9] through spin-orbit coupling or triplet-triplet energy transfer [11][12][13][14] from the dopant to the conjugated polymer in the blended system.…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, a 35 times higher of PCE was obtained in polymer/fullerene device by coordinating 50 mol% of Ir complex to conjugated backbone of poly(fluoreneco-phenylpyridine) due to the formation of the triplet state in Ir containing polymers. 41 Previously, we reported the conjugation of a triplet Ir complex (feed ratio: 1 mol%) to the famous high efficiency donor polymer PTB7. The PCE was found to be significantly increased compared to the Ir-free control polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic materials in organic optoelectronic devices such as organic light emitting diodes (OLEDs), organic transistors, organic solar cells (OSCs) and organic-hybrid solar cells is an area of increasing research interest [1]. The advantages of using organic materials are reduced cost of fabrication, easy processing, large scale production and compatibility with flexible substrates [2][3][4].…”
Section: Introductionmentioning
confidence: 99%